Identification Clean Water Sources in Mining Areas at Amohola Village Moramo sub-district South Konawe - Firdaus; Awaliah Nafiu, Wd Rizky; Anshari, Erwin; Wahab; Deniyatno; Mili, Marwan Zam (Majalah Pengabdian Indonesia, 2025)
In order to meet the daily water needs of the Amohola Village community who currently rely on dug well water mixed with sediment and odor, community service has been carried out by the Mining Engineering Department of Halu Oleo University. The purpose of this service is to find clean water sources through groundwater exploration using the geoelectric method. Based on the results of groundwater measurements with the geoelectric method, it can be interpreted that the groundwater aquifer is located at a depth of 15-45 meters, with a low resistivity value of 371 ohm.m. This indicates that this groundwater layer can be considered a depressed aquifer, which is characterized by low resistivity. The low resistivity is likely caused by impermeable rock types such as clay around the aquifer. Based on these findings, it is recommended that the village government and community conduct groundwater drilling at a depth of 15 to 45 meters. By drilling at this depth, it is hoped that the Amohola Village community can gain access to a safer and higher quality clean water source for their daily needs. In the drilling process, it is also necessary to pay attention to technical and environmental factors to ensure the success of this project and preserve the local environment.